Neutrophil-derived proteases act as global regulators of IL-1 family cytokine activation states - Clancy, Danielle (Trinity College (Dublin, Ireland). Department of Genetics, 2016)
IL-1 family cytokines are pleiotropic cytokines capable of eliciting robust proinflammatory cytokine and chemokine secretion from a broad variety of cell types and tissues. Recent evidence has strongly implicated IL-36 type cytokines, members of the IL-1 family, as key initiators of inflammation in the skin barrier. IL-36 sub-family cytokines belong to the extended IL-1 family and, similar to most members of this family, are expressed as inactive precursors that require proteolytic processing for activation. In chapter 3, we describe the development of a method for the production of biologically active IL-36 through introduction of a caspase cleavage motif, DEVD, within the N-termini of these cytokines. Caspase-3-processed DEVDIL-36 cytokines exhibited robust biological activity on a range of responsive cell types, including primary keratinocytes. These modified forms of IL-36 were used to elucidate molecules involved in the IL-36 receptor signalling pathway. Here, we identify that MyD88, IRAK4, TRAF6 and p65 are essential mediators of IL-36 signalling, a pathway closely related to IL-1 receptor signalling. We also identify the deubiquitinase OTULIN as a negative regulator of IL-36 signalling. By targeting and degrading linear ubiquitin chains required for optimal IL-36 signalling, OTULIN serves to limit IL-36-induced cytokine and chemokine production.
Keywords: Genetics, Ph.D.; PhD Trinity College Dublin, 2016